Magnetohydrodynamic Simulation of Forced Magnetic Reconnection - Masom Sarkhosh; Mahboub Hosseinpour; Mohammad Ali Mohammadi (Iranian Journal of Astronomy and Astrophysics)
Magnetic reconnection is a fundamental process in laboratory, astrophysical, and space plasmas, which is a mechanism for converting magnetic energy into the thermal and kinetic energy of plasma and the efficient acceleration of charged particles. Using two-dimensional magnetohydrodynamic simulations, we investigate the onset and the growth of instability associated with the forced magnetic reconnection phenomenon in the well-known equilibrium structure of the Harris current sheet in the presence of a resistive plasma. To derive externally the magnetic reconnection process, we perturb the velocity of plasma close to the up and down boundaries in the form of two localized pulses. The results show that these pulses propagate towards the current sheet, where the magnetic field changes direction, generates a perturbed magnetic field consequently, and triggers the magnetic reconnection phenomenon in an X-point in the center of the current sheet. We realized that increasing the amplitude of pulses results in a faster reconnection, and symmetric pulses are more efficient in conducting the reconnection. Furthermore, by imposing a transient (time-dependent) MHD wave normal to the current sheet, we found that an MHD wave with a more significant period (lower frequency) considerably affects the current sheet's topology and excites a faster reconnection. A similar conclusion was also obtained for an MHD wave with a larger wavelength (lower wavenumber). The obtained results are of interest for understanding the interaction of an MHD wave with an equilibrium current sheet in confined fusion plasmas and solar corona plasmas.